ユキ ノ アッシュク ネンセイ ト ソノ キコウガクテキ イミ ダイ1カイ ナンキョク キスイケン シンポジウム - 前野, 紀一; マエノ, ノリカズ; 成田, 英器; ナリタ, ヒデキ; MAENO, Norikazu; MAEDA, Hideki (国立極地研究所, 1979)
P(論文) 日本南極地域観測隊か得た,みずほ基地の雪の密度のデータ数は,第11次,第12次および第13次のものを合計すると3635にのぼる.これらの測定結果を吟味,整理したものを使って「圧縮粘性係数」の深さ分布が求められた.みずほ基地の雪に限らず,一般に極地の雪の圧縮粘性係数は,季節的積雪,たとえば北海道の雪に比べて約100倍大きい.これは,極地における長期間の圧密過程において,氷粒子間の結合が極度に成長したためと解釈されるみずほ基地の雪において,密度の測定値は,深さ約30m～40mの領域で,大きく振動し,かつ平均的傾向曲線からはずれた.圧縮粘性係数は,この深さ領域で鋭い極大を示した.これらの結果は,この層の雪が蓄積した時,年間蓄積量の少ない寒冷な時期が繰返しかつ持続して襲来したことを示唆する.その時期は,雪の年間蓄積量から約300年前と推定される. The compactive viscosity coefficient of snow was obtained from a density profile at Mizuho Station, Antarctica The value of the compactive viscosity coefficient was by two orders of magnitude larger than that of ordinary seasonal snow. The large value was attributed to strong bonds between constituent ice particles within Antarctic snow which had been aged for prolonged periods A sharp peak of the compactive viscosity coefficient was found in a limited range of the depth around 35 m, that is in a range of the density around 750 kg m^<-3> In the depth range from 30 m to 40 m the layer-to-layer densities varied largely and the mean density deviated markedly from a smoothed general trend. These results suggest that a colder climate occurred repeatedly and lasted approximately 300 years before the present in the vicinity of Mizuho Station departmental bulletin paper